PENGARUH KEPERCAYAAN KONSUMEN DAN PENGALAMAN PEMBELIAN TERHADAP MINAT BELI KONSUMEN SECARA ONLINE DI KALANGAN MASYARAKAT SANGATTA (STUDI KASUS PADA E-COMMERCE SHOPEE) - Rizkiawan Rizki (Jurnal Eksis, 2020)
This study aims to determine the extent to which supports the Consumer Confidence and Buying Experience of Interest in Buying online. The number of samples used was 55 people selected using Non-Probability Sampling using the Accidental Sampling techinique through a shared questionnaire using the Google Form Application and the contens of the people who live in Sangatta. Analysis of the data used in this research is descriptive analysis, using Multiple Linear Regression Analysis.The results of multiple linear regression analysis namely, Y = 0.489 + 0.672 X1 + 0.485 X2. The most influential independent variable on the dependent variabel is Consumer Confidence (0.672), Purchasing Experience (0.485). t test results show that Consumer Confidence and Purchasing Experience have a positive and significant effect on Puchase Interest. The Coefficient of determination obtained from the independent variables in this study was 77.8 percent. While the remaining 22.2 percent was influenced by other variabels outside the research model. Keywords : Consumer Confidence, Purchasing Experience and Buying Interest